A Primary Hyperparathyroidism in an Adolescent Female with Pathological Fractures and Multiple Bone Lesions Due to Parathyroid Adenoma: Case Report - Harsh Pratap Singh; Chetan Singh; Kishore Parihar; Ankita Parmar; Sanavvar Ali; Anmol Chaurasia (Journal of Orthopaedic Case Reports)
Introduction: Primary hyperparathyroidism (PHPT) is a rare endocrine disorder in adolescents, characterized by excessive parathyroid hormone (PTH) secretion leading to hypercalcemia and various systemic manifestations. Case Report: We present a case of a 19-year-old female with PHPT secondary to parathyroid adenoma, who initially presented with right distal thigh pain and pathological fracture. A diagnostic workup revealed hypercalcemia, elevated PTH levels, and multiple osteolytic lesions throughout her skeletal system. Radiological imaging confirmed extensive bone involvement, including lytic lesions in the femur, phalanges, and skull. Surgical exploration and parathyroidectomy were performed, with histopathology confirming adenoma. Postoperative management included calcium supplementation to manage transient hypocalcemia. Conclusion: This case underscores the diagnostic challenges and aggressive skeletal manifestations of PHPT in young patients, emphasizing the importance of early recognition and intervention to prevent long-term complications.